The loneliness of Sonia and Sunny : a novel [large type] - Desai, Kiran, 1971- (Thorndike Press large print dynamic drama., 2026)
"When Sonia and Sunny first glimpse each other on an overnight train, they are immediately captivated, yet also embarrassed by the fact that their grandparents had once tried to matchmake them, a clumsy meddling that only served to drive Sonia and Sunny apart. Sonia, an aspiring novelist who recently completed her studies in the snowy mountains of Vermont, has returned to her family in India, fearing she is haunted by a dark spell cast by an artist to whom she had once turned for intimacy and inspiration. Sunny, a struggling journalist resettled in New York City, is attempting to flee his imperious mother and the violence of his warring clan. Uncertain of their future, Sonia and Sunny embark on a search for happiness together as they confront the many alienations of our modern world."--